HARMONISASI PERATURAN DAERAH KABUPATEN/KOTA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 137/PUU-XIII/2015 - Muhammad Roqib (Universitas Muhammadiyah Gresik, 2021)
Constitutional Court has issued Verdict No. 137/PUU-XIII/2015 about withdrawing the Governor’s authority in cancelling regency/city regulation. The Constitutional Court has tested Article No. 251 (2), (3), (4), and (8) on the Constitution No. 23 of 2014 about Local Government. By this verdict, the only way to issue the cancellation of the regency/city regulation is through judicial review mechanism of Supreme Court (MA). Only after the Governor’s authority in cancelling the regency/city regulation has been revoked, a problem appears in how to ensure the harmonization between the regency/city regulation and another regulation. This research uses statute approach, examining all of the constitutions with examined law issues and conceptual approach which starts from points of view and developing doctrines in science of law. Based on this research result, it is discovered that during the implementation of the Verdict of the Constutional Court No. 137/PUU-XIII/2015 did not deprive the control of central government towards local government, including the establishment of regency/city regulation. Governor as representative of central government in the region was given an authority to supervise preventively towards the establishment of regency/city regulation. By maximum preventive supervision, it would harmonize between regency/city regulation and another constitutional regulation.